TRAILBLAZER‐ALZ Study: Dynamics of amyloid reduction after donanemab treatment. (31st December 2021) - Shcherbinin, Sergey; Andersen, Scott W.; Evans, Cynthia Duggan; Lo, Albert C.; Lu, Ming; Navitsky, Michael; Collins, Emily C; Sims, John R.; Brooks, Dawn A.; Mintun, Mark A
Abstract: Background: Accumulation of amyloid‐β (Aβ) peptide in amyloid plaques is a pathological hallmark of Alzheimer's disease (AD). Reduction of Aβ could slow the progression of AD. Donanemab is an antibody specific for the N‐terminal pyroglutamate Aβ epitope that is only present in mature brain amyloid plaques. In the TRAILBLAZER‐ALZ study, 67.8% (n=61) of donanemab‐treated participants became amyloid negative by 76 weeks. Here we further characterize amyloid reduction after donanemab treatment. Method: Participants (placebo N=84, donanemab N=69) that completed 4 florbetapir scans in TRAILBLAZER‐ALZ were analyzed for amyloid reduction rate, measured in centiloids (CL). Donanemab dosing was 700mg every 4 weeks (Q4W) for the first 3 doses, then 1400mg Q4W, for up to 76 weeks. Planned blinded dose reduction evaluations occurred at 24 and 52 weeks creating three periods of time between florbetapir scans: baseline‐24wk, 24wk‐52wk, or 52wk‐76wk. ANOVA were performed to compare baseline parameters. Result: At 24wk, 15 participants in the donanemab group were assigned to 700mg dose and 19 were assigned to placebo. At 52wk, 10 participants were assigned to 700mg dose and 8 were assigned to placebo. In the 17 participants that remained on 1400mg donanemab until the end of the trial, amyloid reduction rate decreased during baseline‐24wk, 24wk‐52wk, and 52wk‐76wk (mean (SD): ‐2.7(1.5), ‐1.0 (0.7), and ‐0.5 (0.5) CL/wk, respectively). At the end of the trial, 5 out of 17 participants that remained in the 1400mg group became amyloid negative. In the 15 participants that were assigned to 700mg at 24wk, plaque lowering rate decreased from an average of ‐3.0 (1.2) CL/wk over the first 24wk to an average of ‐0.4 (0.4) CL/wk over 24wk‐52wk. At the end of the trial, 13 participants assigned to 700mg donanemab Q4W at 24wk became amyloid negative. Patients that received placebo at 24wk‐76wk (n=19) or 52wk‐76wk (n=19), had no re‐accumulation (mean (SD): 0.0 (0.1) CL/wk and ‐0.1 (0.2) CL/wk, respectively). Participants that stayed on 1400mg until study end had higher baseline amyloid (p=0.0000) and tau (p=0.0488) and were younger (p=0.0472) than those assigned to 700mg or placebo at 24wk. Conclusion: Donanemab treatment reduced amyloid plaques and resulted in no re‐accumulation of amyloid over 1 year.